Hasil Tanaman Jagung yang Dipupuk N, P, dan K di Dutohe Kabupaten Bone Bolango - Aluwi, Febrian F. R.; ., Nurdin; Jamin, Fitriah S. (Jurnal Agroteknotropika, 2012)
The objective of this research was to study the respons of N, P, and K fertilizers and the best combination of it on the maize yields. The experimental design was following random block design that consist of 4 treatments with 3 replications, so there are 12 plot units. Dosages of each treatment were 160 kg Urea, 54 kg TSP, and 90 kg KCl. The result of this research showing that minus one test has significant effect to stem length, stem diameters, and all dry weigh, for 100 gain weigh has not significant effects. The best treatment combination was N+K treatment or minus P.